2017
DOI: 10.1038/s41467-017-00983-w
|View full text |Cite
|
Sign up to set email alerts
|

TRPA1–FGFR2 binding event is a regulatory oncogenic driver modulated by miRNA-142-3p

Abstract: Recent evidence suggests that the ion channel TRPA1 is implicated in lung adenocarcinoma (LUAD), where its role and mechanism of action remain unknown. We have previously established that the membrane receptor FGFR2 drives LUAD progression through aberrant protein–protein interactions mediated via its C-terminal proline-rich motif. Here we report that the N-terminal ankyrin repeats of TRPA1 directly bind to the C-terminal proline-rich motif of FGFR2 inducing the constitutive activation of the receptor, thereby… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 59 publications
2
29
0
Order By: Relevance
“…The roles and mechanisms of miR-142-3p in NPC metastasis remain undefined. We demonstrated that miR-142-3p functioned as a suppressor in NPC metastasis, which is consistent with the inhibitory effects of miR-142-3p in other cancer types [31][32][33]. However, previous study showed a conversely promoted phenotype of miR-142-3p in NPC cell proliferation [34].…”
Section: Discussionsupporting
confidence: 87%
“…The roles and mechanisms of miR-142-3p in NPC metastasis remain undefined. We demonstrated that miR-142-3p functioned as a suppressor in NPC metastasis, which is consistent with the inhibitory effects of miR-142-3p in other cancer types [31][32][33]. However, previous study showed a conversely promoted phenotype of miR-142-3p in NPC cell proliferation [34].…”
Section: Discussionsupporting
confidence: 87%
“…MicroRNAs are non-coding RNAs which participate in cellular activity by regulating target genes. Increasing number of studies have reported that microRNAs are frequently differentially expressed in numerous types of human cancer and play an important role in the progression and development of NSCLC ( Inamura and Ishikawa, 2016 ; Berrout et al, 2017 ; Chang et al, 2017 ; Zhang et al, 2017 ; Iqbal et al, 2018 ). Although microRNAs act only in the cell where they are synthesized, they can also influence the functions of neighboring cells or play a role in the tumor micro-environment by modulating the ECM state ( Rutnam et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we chose a rabbit extracellular TRPA1 antibody for several reasons: (1) this antibody has been well characterized by the vendor, demonstrating a high specificity against an epitope (NSTGIINETSDHSE) corresponding to amino acid residues 747 to 760 in the first extracellular loop of TRPA1 ( Figure 1a); (2) the specificity has been verified in TRPA1 knockout tissue; 38 and (3) it consistently detects TRPA1 expression by IHC or immunoblot from DRGs and from nonneuronal tissues. 19,[36][37][38]40,[53][54][55][56][57][58][59][60][61][62][63] We also tested the specificity of this antibody in the detection of TRPA1 expression. By immunoblot, the antibody revealed a clean band at $120 KDa as the target protein in the homogenates of the DRGs from adult rats, and preincubation with excess immunogenic peptide completely eliminated the band (Figure 1b).…”
Section: Trpa1 Is Expressed In Primary Sensory Neurons Sgcs and Scsmentioning
confidence: 99%